Prevalence and Risk Factors of Suspected Case Primary Bloodstream Infection in Chronic Renal Failure Patients with Catheter Double Lumen at Dr. Mohammad Hoesin General Hospital Palembang - Sholekhuddin Wahyu; Kemas Muhammad Dahlan; Jaka Fahmi; Novadian; Theodorus (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2022)
Background: Primary bloodstream infection (BSI) is an infection that occurs without any other organ or tissue suspected as a source of infection. BSI is often found in patients who have a catheter double lumen (CDL) attached device. The use of CDL causes a lot of risk of infection in patients with renal failure. Factors that influence the occurrence of BSI can be endogenous and exogenous factors. This study aimed to determine the prevalence rate and the factors that influence BSI in chronic renal failure patients with double-lumen catheters undergoing hemodialysis at the Dr. Mohammad Hoesin General Hospital, Palembang. Methods: This study was an analytical observational study with a cross-sectional design undertaken in the hemodialysis unit, medical record installation, and clinical laboratory of Dr. Mohammad Hoesin General Hospital Palembang from February to December 2021. There were 93 patients who met the inclusion criteria. The relationship between risk factors and the incidence of BSI was analyzed using the Chi-Square and Fisher Exact tests. All data were analyzed by SPPS version 22.0. Results: In this study, 44 people (47.3%) had primary bloodstream infection (BSI). In addition, there was a significant relationship between gender (PR = 2.508 (CI5% 1.087 – 5.784); p = 0.049); BMI (PR = 6.150 (CI5% 2.349 – 16.099); p = 0.000); and catheter type (p = 0.000) with the incidence of BSI. However, there was a non-significant relationship between age, catheter location, and duration of catheter insertion with the incidence of BSI (p > 0.05). Conclusion: Body mass index and gender are risk factors for primary bloodstream infection.